Efektivitas Media Interaktif Berbasis Articulate Storyline 3 Materi Ekosistem pada Siswa Kelas V Sekolah Dasar - Aulia, Fatwa; Sulistiawati, Siti; Anjab Munjaji, Muhammad; Heryadi, Yadi (LPPM Universitas Bina Bangsa, 2025)
This study aims to explore the effectiveness of interactive media based on Articulate Storyline 3 in improving students' understanding of the concept of ecosystems in Natural and Social Sciences (IPAS) learning in grade V of Pasir Keong State Elementary School. The research background is based on the low level of students' understanding of the concept of ecosystems, the dominance of conventional learning methods, and the lack of optimal use of interactive digital media in the classroom. This study uses a descriptive qualitative approach, data is collected through observation, questionnaires, interviews, and documentation involving teachers and students as participants. Data analysis is carried out through data reduction, data presentation, and conclusion drawing and verification. The results of the study show that interactive media based on Articulate Storyline 3 is able to increase student involvement, enthusiasm, and understanding in learning ecosystem materials. Interactivity in this medium provides an effective learning stimulus, making it easier for students to understand abstract concepts such as food chains and ecosystem balance. This study concludes that Articulate Storyline 3 is a relevant, effective, and adaptive learning medium to support the 21st century learning process that demands innovation and technology-based approaches